Perspectives and experiences of Zambian pregnant and postpartum women receiving two intervention models to increase uptake of male partner HIV testing - Oliver Mweemba; Suzanne Maman; Kellie Freeborn; Caroline Hazwela; Aditi Kamat; Andrew Kumwenda; Mildred Lusaka; Tulani Francis L. Matenga; Nachizya Edith Namukanga; Nora E. Rosenberg; Benjamin H. Chi; Wilbroad Mutale (Taylor & Francis Group, 2023)
This study explored the experiences of pregnant women who received two intervention models for increasing uptake of male partner HIV testing in antenatal settings. As part of a randomised trial, we interviewed twenty participants who received partner notification services only while 22 received the partner notification plus HIV self-testing. Thematic analysis was used to analyse the data. Partner notification services helped to initiate discussions of HIV testing with partners, influence partners to undergo testing, and encouraged disclosure of HIV status. Some women experienced difficulties engaging partners due to fear of their partner's reaction. Some partners were unable to test due to time constraints. The partner notification plus HIV self-testing intervention, stimulated discussion about HIV testing; facilitated testing for men at their convenience; addressed privacy/confidentiality, and stigma concerns; and provided the opportunity to disclose HIV status. Some women feared disclosure and retribution in case of discordance results. There were also challenges with men making follow-ups for confirmatory HIV tests. The addition of HIV self-test kits to partner notification services can expand HIV testing services to male partners, including those of HIV-negative women. Additional efforts are needed to link men to appropriate HIV prevention, care, and treatment services.